The Collapse of Communism as the End of the Modernity Project? Post-Soviet Transformation Narratives of the Lithuanian Population - Ramonaitė, Ainė; Vijeikis, Paulius (Politologija, 2023)
The article analyses how Lithuanian inhabitants remember and assess the post-communist transformation and searches for the narratives that can be interpreted through the lens of modernization theories. The paper draws on a dataset of 43 biographical interviews collected in 2021 in Panevėžys city and Panevėžys district. Employing the method of thematic narrative analysis, four dominant narratives of post-soviet transformation were identified: “demodernization”, “real modernization”, “continuation of neo-traditionalism” and “continuation of modernity”. In the narrative of “demodernization”, the Soviet regime is seen as the true modernity, and the post-Soviet transformation is perceived as a process of demodernization, when progress is replaced by stagnation or regression, manifested in the decline of industry and the disappearance of other attributes of modernity. In the narrative of “true modernity”, on the contrary, the Soviet era is seen as a false or failed modernity characterized by inefficiency and backwardness, and the features of modernity are attributed to the new order emerging after the restoration of independence. The narratives of “continuity of neo-traditionalism” and “continuity of modernity” observe similar features in both the Soviet era and the period of transformation, but the former emphasizes the neo-traditionalist or “anti-modern” features of both periods, such as inefficiency, corruption, and privilege, while the latter sees both periods as progressive in their own ways.